The effect of intravitreal injection of Bevacizumab on the corneal endothelium (Latakia University Journal -Medical Sciences Series, 2022)
Purpose:To assess the effect of intravitreal injection of bevacizumab on corneal endothelial cell count and morphology.Methods: This prospective study was carried out at Tishreen University Hospital between the years 2021-2022. A total of 93 eyes from 66 patients with chorioretinal vascular diseases were studied, they were divided into three groups according to the number of intravitreal injections of bevacizumab (single injection, two injections, three injections). All participants underwent a complete ophthalmological examination including corneal endothelial cell counts by non-contact specular microscopy, where the average of three successive measurements of endothelial cell density (ECD), coefficient of variation (CV), hexogram (EX%) and central corneal thickness (CCT) were taken. Results before injection, one month after each injection and six months after the first injection were compared.Results: There were no statistically significant differences in corneal endothelial cell density before injection or one month after each injection or six months after the first injection in the three study groups. In comparison between the values before and after injection in the three groups, there were also no statistically significant differences in each of coefficient of variation (CV), hexagonal cells percentage (EX%) and central corneal thickness (CCT).Conclusion: Intravitreal injection of bevacizumab once or monthly for two or three consecutive months does not affect corneal endothelial cells morphology or density and has no harmful effects on the endothelium.Keywords: Bevacizumab, corneal endothelial cells, intravitreal injection, specular microscopy, vascular endothelial growth factor.